2019
DOI: 10.3892/etm.2019.7197
|View full text |Cite
|
Sign up to set email alerts
|

Microvesicles containing miR-34a induce apoptosis of proximal tubular epithelial cells and participate in renal interstitial fibrosis

Abstract: Function and potential mechanism of microvesicles (MVs) containing microRNA34a in renal interstitial fibrosis were investigated. A rat model of renal interstitial fibrosis was established by unilateral ureteral ligation (UUO). Rat proximal tubular epithelial cell line (NRK-52E) was used to explore the effect of MVs containing microRNA-34a on tubular epithelial cells during fibrosis, which were secreted by tubulointerstitial fibroblasts. Regardless of the UUO renal interstitial fibrosis model, or the TGF-β1-tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…The majority of these miRNAs have previously been linked to renal diseases, such as RIF. For example, Hou et al (33) found miR-27a to suppress peroxisome proliferator-activated receptor-γ signaling and to thereby promote RIF, whereas miR-34a has been shown to regulate Klotho expression in tubular epithelial cells, thereby controlling RIF (34), while also inducing the apoptotic death of these cells (35). There is also evidence to indicate that miR-214 is upregulated in the context of renal injury, and the knockdown of this miRNA is sufficient to attenuate unilateral ureteral obstruction (UUO)-induced RIF (36).…”
Section: Discussionmentioning
confidence: 99%
“…The majority of these miRNAs have previously been linked to renal diseases, such as RIF. For example, Hou et al (33) found miR-27a to suppress peroxisome proliferator-activated receptor-γ signaling and to thereby promote RIF, whereas miR-34a has been shown to regulate Klotho expression in tubular epithelial cells, thereby controlling RIF (34), while also inducing the apoptotic death of these cells (35). There is also evidence to indicate that miR-214 is upregulated in the context of renal injury, and the knockdown of this miRNA is sufficient to attenuate unilateral ureteral obstruction (UUO)-induced RIF (36).…”
Section: Discussionmentioning
confidence: 99%
“…Overall the results provide evidence in support of beneficial properties of EVs from various sources in prevention or treatment of kidney disorders. However, some EVs secreted by TECs [68][69][70][71][72][73] , fibroblasts 84,85 , platelets 86,87 , podocyte 96 , and MM cells 97 were found to have adverse effects on renal function. Five other studies also suggested that EVs from fibroblasts 25,37,40,77 and T-CD133 + cells 95 may have no beneficial effects on renal injury protection.…”
Section: Discussionmentioning
confidence: 99%
“…Microvesicles, a new cell signaling vector for short- or long-range delivery, contains protein, mRNA and miRNA ( Martins et al, 2013 ; Recep et al, 2017 ). In a study of renal fibrosis, it has been found that ( Zhou et al, 2014 ; Li et al, 2019 ) renal interstitial fibroblasts can secrete microvesicles containing miR-34a to transport to renal tubular epithelial cells and promote their apoptosis; then the microbubbles in fibroblasts can be extracted and injected into cells or mice to imitate the mechanism of miR-34a in renal fibrosis. With the development of science and technology, other better biological agents will likely be found in the future, further improving the treatment of FB.…”
Section: Limitation Of Microrna-34a As Therapeutic Targets Of Fibrosismentioning
confidence: 99%
“…Tubular epithelial cells apoptosis is one of the mechanisms of tubular atrophy and tubulointerstitial fibrosis ( Docherty et al, 2006 ). In the study of rats and mice with renal interstitial fibrosis, miR-34a was released from mesenchymal fibroblasts and transferred to proximal tubular epithelial cells, where it promoted apoptosis of renal tubular epithelial cells by inhibiting the transcription and translation of Bcl-2, further aggravating renal interstitial fibrosis ( Zhou et al, 2014 ; Li et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%